Breaking age barriers: the efficacy of ERCP in advanced age patients - Zhuang Li; Zhenyu Qiao; Wenfei Wang; Yanjun Sun; Dengqun Sun; Minghui Sheng (BMC Surgery)
Abstract Background This study aims to evaluate the efficacy and safety of therapeutic endoscopic retrograde cholangiopancreatography (ERCP) in patients aged 75 years and older. Methods A total of 723 patients who underwent ERCP at Anhui Provincial Corps Hospital of the Chinese People’s Armed Police Force between March 2018 and April 2022 were retrospectively analyzed. This cohort included 152 patients aged ≥ 75 years (elderly group) and 571 patients aged < 75 years (control group). A 1:1 propensity score matching method was used to match the baseline characteristics of gender, stone number, and stone size between the two groups to obtain a covariate balanced sample, resulting in 152 successfully matched cases. Data on comorbidities, surgical procedures, clinical outcomes, and ERCP-related complications were collected and compared between the two groups. Results The elderly cohort exhibited a significantly higher prevalence of comorbidities, including hypertension, diabetes, abnormal liver function, and cardiovascular and pulmonary diseases, when compared to the control group (p < 0.05). The primary indication for ERCP in both groups was choledocholithiasis. However, the elderly group had a notably higher incidence of a history of cholecystolithiasis and cholecystectomy (p < 0.05). The stone removal success rate was 95.39% (145/152) in both groups, and the difference between the groups was not statistically significant (P = 1). The rate of postoperative complications was 11.84% (18/152) in the elderly group and 18.42% (28/152) in the control group, with no significant difference observed (P = 0.11). Both groups demonstrated an improvement in quality of life scores following ERCP, with the elderly group showing significantly higher scores compared to the control group (p < 0.05). Long-term follow-up revealed that the recurrence of choledocholithiasis and cholangitis increased over time in the elderly group; however, no significant difference in recurrence rates was noted between the two groups (P > 0.05). Conclusions ERCP is a safe and effective therapeutic approach for elderly patients with choledocholithiasis, associated with a low incidence of complications and favorable clinical outcomes. Given its efficacy and safety profile, ERCP should be considered a treatment of choice for elderly individuals with choledocholithiasis.